STUDIES OF THE EFFECT OF BACTERIAL ENDOTOXINS ON RABBIT LEUCOCYTES : II. DEVELOPMENT OF ACQUIRED RESISTANCE - Cluff, Leighton E. (The Rockefeller University Press, 1953)
Bacterial endotoxin injected intravenously into rabbits inhibited the migration of leucocytes from the buffy coat of centrifuged blood (4). Repeated daily injections of endotoxin resulted in the rabbits becoming resistant to the fever-inducing action of the toxin, and migration of leucocytes from centrifuged blood was no longer inhibited by injection of the toxin. Leucocyte migration from the buffy coat of centrifuged blood after injection of toxin into the rabbits appeared gradually over the first few days of repeated injections, and disappeared during the 10 to 15 days after cessation of daily injections of toxin. The resistance to endotoxin, demonstrated by leucocyte migration and pyrogen tolerance, could not be passively transferred with serum from resistant animals, and was non-specific, in that resistance to one endotoxin conferred some resistance to toxin from an organism of a different species. No relationship could be demonstrated between precipitin titer and resistance. Thorotrast abolished resistance to the fever-inducing activity of endotoxin, but its effect on leucocyte resistance was not clear, since when injected alone it inhibited migration of leucocytes from the buffy coat of centrifuged blood. The suggestion is made that the failure of toxin to inhibit the migration of leucocytes from resistant rabbits is due either to the presence of leucocytes which have become adapted to the toxin by repeated exposure, or to rapid removal of the toxin by the reticulo-endothelial system. It is unlikely that leucocyte resistance participates in the development of tolerance to the fever-inducing action of endotoxin. However, in view of the participation of the leucocyte in the pathogenesis of the Shwartzman reaction, the presence of leucocytes resistant to endotoxin may be responsible in part for the development of resistance to the Shwartzman phenomenon.